2016
DOI: 10.1002/rra.3059
|View full text |Cite
|
Sign up to set email alerts
|

Dam Operations Affect Route-specific Passage and Survival of Juvenile Chinook Salmon at a Main-stem Diversion dam

Abstract: Diversion dams can negatively affect emigrating juvenile salmon populations because fish must pass through the impounded river created by the dam, negotiate a passage route at the dam and then emigrate through a riverine reach that has been affected by reduced river discharge. To quantify the effects of a main-stem diversion dam on juvenile Chinook salmon in the Yakima River, Washington, USA, we used radio telemetry to understand how dam operations and river discharge in the 18-km reach downstream of the dam a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 32 publications
2
12
0
Order By: Relevance
“…Fish injury or death could occur at these locations when the opening is relatively small, which may increase the likelihood of fish striking the gate, encountering unsafe hydraulic conditions, or being injured by debris that accumulates or collects immediately downstream of the gate. There is evidence to support this theory from a previous study (Perry et al 2016) at Roza Dam, located upstream of our study area on the Yakima River. During that study, researchers found that fish survival through the East Gate, which operates similarly to a radial gate, declined severely during low-flow operations when the gate opening was greatly reduced (Perry et al 2016).…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Fish injury or death could occur at these locations when the opening is relatively small, which may increase the likelihood of fish striking the gate, encountering unsafe hydraulic conditions, or being injured by debris that accumulates or collects immediately downstream of the gate. There is evidence to support this theory from a previous study (Perry et al 2016) at Roza Dam, located upstream of our study area on the Yakima River. During that study, researchers found that fish survival through the East Gate, which operates similarly to a radial gate, declined severely during low-flow operations when the gate opening was greatly reduced (Perry et al 2016).…”
Section: Discussionsupporting
confidence: 85%
“…Fish that are eventually screened from the canal and returned to the river must also interact with several infrastructure components (trash racks, fish screens, bypass pipes), which could also result in injury or death. During the Perry et al (2016) study, survival through the fish bypass at Roza Dam was found to be the lowest of all passage routes across the entire range of streamflows and dam operations. Additionally, other fish species such as Northern Pikeminnow Ptychocheilus oregonensis, Smallmouth Bass Micropterus dolomieu, Channel Catfish Ictalurus punctatus, and Black Crappie Pomoxis nigromaculatus have been observed in canals on the Yakima River and present a constant predation threat to entrained juvenile salmon and steelhead (Beals and Lampman 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The potential impacts of PMBs are often ignored, despite increasing recognition of the potential impacts they pose to migratory fish species (Gowans et al 2003;Scruton et al 2007;Perry et al 2016;Nyqvist et al 2017b;Ovidio et al 2017). This likely reflects the high uncertainty that exists in defining the fish passage efficiency of particular passable barriers (Bunt, Castro-Santos & Haro 2012;Noonan, Grant & Jackson 2012).…”
Section: Discussionmentioning
confidence: 99%